Matematyka
panprzem1
2017-06-24 13:24:17
Doprowadź wyrażenia do najprostszej postaci: a)(2x-3)^2+(3+x)^2 b) (x-4)^2-2(x+1)^2 c) (2x-3)(2x+3)-(4x+1)^2
Odpowiedź
RoseShooter
2017-06-24 15:56:50

a)(2x-3)^2+(3+x)^2=4x^2-12x+9+9+6x+x^2=5x^2-6x+18 b) (x-4)^2-2(x+1)^2=x^2-8x+16-2(x^2+2x+1)=x^2-8x+16-2x^2-4x-2=-x^2 -12x+14 c) (2x-3)(2x+3)-(4x+1)^2 =4x^2-9-16x^2-8x-1=-12x^2-8x-10

kips
2017-06-24 15:58:05

(a + b)² = a² + 2ab + b² (a - b)² = a² - 2ab + b² (a + b)(a - b) = a² - b² [latex]a)\(2x - 3)^{2}+ (3+x)^{2} = 4x^{2}-12x+9+ 9 + 6x + x^{2} = 5x^{2}-6x+18 \\b)\(x-4)^{2}-2(x+1)^2} = x^{2}-8x+16-2(x^{2}+2x+1) = \=x^{2}-8x+16-2x^{2}-4x-2 = -x^{2}-12x+14\\c)\(2x-3)(2x+3)-(4x+1)^{2} = 4x^{2}-9-(16x^{2}+8x+1) =\=4x^{2}-9-16x^{2}-8x-1=-12x^{2}-8x-10[/latex]

Dodaj swoją odpowiedź